From Land to Common Territory: : Zapatista ontology in confrontation with the ontocide of capital in the Global South - Pinheiro Barbosa, Lia (2024)
This article presents the concept of territory and the defense of the commons in the light of the political ontology and autonomous struggle of the Zapatista Movement in Mexico. The central argument is that the ontological and epistemic matrices of Zapatista autonomy constitute a fundamental element in confronting ontocide, capital's, historic method of territorial expansion. Furthermore, there are important lessons learned from Zapatista autonomy that can inspire and dialogue with other territorial defense processes underway in the Global South. To this end, I present the political proposal of «territory in common» as a turning point in Zapatismo's analysis of the reconfigurations of capitalism, bringing to light new strategies for confronting capitalism by spoliation in the 21st century.